HANDLING THE ECONOMIC IMPACT OF THE COVID-19 PANDEMIC ON TOURISM VILLAGE AREA - Putra I W.G.Y.D.; Indriyani N.M.V. (Russian Journal of Agricultural and Socio-Economic Sciences, 2021)
The COVID-19 pandemic has had a significant impact on the life of the world community, including in Indonesia. In addition to the health impact, the pandemic also has an economic impact, thus prompting the government to make various policies to overcome these impacts. Policies by optimizing state and regional budgets for the needs of preventing the spread and handling of the health impacts of COVID-19 and optimizing local economic potential meet community needs in a sustainable manner. The potential that can be increased in supporting the village's original income is in the tourism sector. In the concept of a tourist village, the active role of the development and management of a tourist village is in the hands of the village community. In this case, the village community does not become an audience but becomes an active player in managing tourist attractions in their village so that they can finally get economic benefits in the form of increasing Regional Original Income. The purpose of this study is to understand, describe and analyze how the strategy for handling the economic impact of the COVID-19 pandemic is the Taro Village Government. The data analysis techniques used are interviews, literature study and documentation. The data obtained will be analyzed using qualitative descriptive analysis techniques. The results of this study are expected to provide a reference for the Taro Village community regarding the strategy for handling the economic impact of the COVID-19 pandemic, the Taro Village Government.